The importance of sacrifice: new approaches to old methods - Ekroth, Gunnel (Kernos, 2007)
The study of sacrifice in antiquity has recently been enriched by two important contributions in the form of the acta of conferences, one organized at Göteborg in 1997 and the other in Paris in 2001. The scope and aims of these two events were highly different. The Göteborg seminar focused specifically on the Olympian and chthonian aspects of Greek sacrificial ritual, while the Paris conference aimed at evaluating and broadening the work presented in the seminal study La cuisine du sacrifice ...